Integration of Smart Technologies in Teaching in Selected Colleges of Education in North-Eastern Nigeria: Issues and Challenges - Tijjani Usman Karofi (Walidem Institute and Publishing, 2025)
Objective: This study explores the e-preparedness of Colleges of Education in Nigeria in adopting cutting-edge smart technologies for teaching and learning. As institutions responsible for teacher education, these colleges—classified as federal and state-owned—face increasing complexities that necessitate advanced digital competency. The research aims to assess the availability, functionality, and integration of ICT tools in teaching, identifying key challenges and proposing strategic solutions. Theoretical Framework: The theoretical framework is grounded in the ICT ecosystem and its value chain, emphasizing the role of digital technologies in content delivery, professional development, and facility management. Literature Review: A review of relevant literature and empirical studies highlights the transformative potential of ICT in teacher education, while also exposing gaps in digital literacy, internet accessibility, and infrastructure reliability. Methods: A structured questionnaire was designed, validated, pilot-tested, and administered to a selected sample. The study employed T-test statistical analysis at a 0.05 significance level to test the research hypothesis. Results: Findings indicate that while ICT facilities are available, functional, and accessible, the integration of smart technologies in teaching remains suboptimal. Key barriers include inadequate digital literacy, unstable internet access, irregular power supply, insufficient technical expertise, and outdated technological resources. Implications: The study's implications suggest an urgent need for a well-defined ICT development policy tailored to the specific needs of Colleges of Education. Recommendations include consistent power supply, continuous professional development for educators, network infrastructure upgrades, and sustainable internet subscriptions. Novelty: The novelty of this research lies in its empirical assessment of e-preparedness in Nigerian teacher education institutions, providing actionable insights for policy formulation and institutional enhancement. By addressing critical digital gaps, the study contributes to the ongoing discourse on technology-driven education reform in Nigeria.